ANTIOXIDANT ACTIVITY OF TARENNA POLYCARPA (MIQ.) KOORD. LEAF - Sari, Rika Puspita; Nainggolan, Marline; Rosidah, Rosidah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study is to evaluate the antioxidant activity of Tarenna polycarpa (Miq.) koord. Ex Valenton. Leaf extract and fractions. Methods: Antioxidant activity was examined by DPPH method. Results: Ethanol extract, n-hexane fraction, and ethyl acetate fraction with DPPH assay measured as half maximal inhibitory concentration were 55.21, 109.73, and 42.04 Î¼g/mL, respectively. Conclusions: The results reveal that T. polycarpa extract and fractions have strong antioxidant potential. Our further study is to isolate compounds responsible for antioxidant components.